On Ethnoerotism in Cross-Cultural Perspective: Mythology, Poetics, and National Genesis in Latin America, Romania, and Ancient Rome - Gheorghiță Geană (Genealogy, 2025)
The term “ethnoerotism” is advanced for expressing the attraction and union between two ethnic groups placed under the gender symbols—male and female—that contribute, with their specific energies, to the genesis of a new people or nation. By using some concepts as “myth” and “ethnosymbolism”, this outlook regarding the origin of nations is exemplified by Natividad Gutiérrez (with the descent of nations in Latin America), Vasile Pârvan (with a poem in prose about the genesis of the Romanian people), and Titus Livius and Plutarch (with the abduction of Sabine women after the founding of ancient Rome). These cases are presented in the framework of a vision about the “diachronic dimension of national identity” (Geană 2016). It also should be mentioned that (at least in the Romanian case) such a vision regarding ethnic genesis and continuity in time is passed on from generation to generation by a vivid folk tradition, as well as, in modern times, by the official system of education.